Hydroxysafflor Yellow A Attenuates Bleomycin‐induced Pulmonary Fibrosis in Mice. (18th January 2016) - Jin, Ming; Wu, Yan; Wang, Lin; Zang, Baoxia; Tan, Li
Abstract : Hydroxysafflor yellow A (HSYA) is an active component of Carthamus tinctorius L., and we want to investigate whether HSYA attenuates pulmonary fibrosis induced by bleomycin (BLM) in mice. The mice received a BLM via oropharyngeal aspiration, and HSYA was intraperitoneally injected. Arterial blood gas analysis was performed. Morphological changes and hydroxyproline content were measured. mRNA expression of transforming growth factor‐β1 (TGF‐β1), connective tissue growth factor, α‐smooth muscle actin (α‐SMA), and collagen I was measured by real‐time polymerase chain reaction. α‐SMA‐positive cells in lung tissues were detected by immunohistochemical staining. A549 cell was cultured, and morphological changes were observed after TGF‐β1 and HSYA treatment. mRNA expression was detected by real‐time polymerase chain reaction. Phosphorylation of Smad3 was evaluated by western blotting. HSYA decreased the lung consolidation area and collagen deposition in mice with pulmonary fibrosis. The blood gas changes due to BLM were attenuated by HSYA. HSYA also alleviated the BLM‐induced increase of TGF‐β1, connective tissue growth factor, α‐SMA, and collagen I mRNA levels. HSYA treatment inhibited the increase of α‐SMA expression, Smad3 phosphorylation, the morphological changes in lung tissue. HSYA inhibits Smad3 phosphorylation and elevated expression of collagen I mRNA in epithelial–mesenchymal transition induced by TGF‐β1. Copyright © 2016 John Wiley & Sons, Ltd.